Factors associated with the timely uptake of initial HIV virologic test among HIV-exposed infants attending clinics within a faith-based HIV program in Kenya; a cross-sectional study - Douglas Gaitho; Freda Kinoti; Lawrence Mwaniki; Diana Kemunto; Victor Ogoti; Catherine Njigua; Elizabeth Kubo; Agnes Langat; Jared Mecha (BMC, 2021)
Abstract Background Early infant diagnosis (EID) of HIV, followed by effective care including antiretroviral therapy (ART), reduces infant mortality by 76% and HIV progression by 75%. In 2015, 50% of 1.2 million HIV-exposed infants (HEI) in 21 priority countries received a virologic test within the recommended 2 months of birth. We sought to identify factors associated with timely uptake of virologic EID among HEI and gain insight into missed opportunities. Methods This was a cross-sectional study that used de-identified data from electronic medical records of 54 health facilities within the Christian Health Association of Kenya (CHAK) HIV Project database. All HEI who had their first HIV virologic test done between January 2015 and December 2017 were included in the study and categorized as either having the test within or after 8 weeks of birth. Multivariate linear mixed effects regression model was used to determine factors associated with uptake of the first HIV EID polymerase chain reaction (PCR). Predictor variables studied include sex, birth weight, the entry point into care, provision of ART prophylaxis for the infant, maternal ART at time of EID, mode of delivery, and place of delivery. Results We included 2020 HEI of whom 1018 (50.4%) were female. A majority, 1596 (79.0%) had their first HIV PCR within 2 months of birth at a median age of 6.4 weeks (interquartile range 6-7.4). Overall, HIV positivity rate at initial test among this cohort was 1.2%. Delayed HIV PCR testing for EID was more likely to yield a positive result [adjusted odds ratio (aOR) = 1.29 (95% confidence interval (CI) 1.09-1.52) p = 0.003]. Infants of mothers not on ART at the time of HIV PCR test and infants who had not received prophylaxis to prevent vertical HIV transmission had significant increased odds of a delayed initial test [aOR = 1.27 (95% CI = 1.18-1.37) p = < 0.0001] and [aOR = 1.43 (95% CI 1.27-1.61) p = < 0.001] respectively. Conclusion An initial HIV PCR test done after 8 weeks of birth is likely to yield a positive result. Barriers to accessing ART for treatment among HIV-infected pregnant and breastfeeding women, and prophylaxis for the HEI were associated with delayed EID. In order to ensure timely EID, programs need to incorporate both facility and community strategy interventions to ensure all pregnant women seek antenatal care and deliver within health facilities.